Determinants of quality of life in Rett syndrome: New findings on associations with genotype - Mendoza, J.; Downs, Jennepher; Wong, K.; Leonard, H. (BMJ PUBLISHING GROUP, 2021)
Background: Rett syndrome is a genetically caused neurodevelopmental disorder associated with functional deficits and comorbidities. This study investigated relationships between genotype, functional abilities and comorbidities and quality of life in Rett syndrome.